2016
DOI: 10.1063/1.4958585
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan concentration and heat treatment on electrospun PVA/Chitosan nanofibers

Abstract: Abstract. Electrospun nanofibers membrane were fabricated from poly(vinyl alcohol)/chitosan (PVA/CS) with a mass ratio of 70/30 and 50/50 in 2% acetic acid solvent by electrospinning method. The morphology of nanofibers membrane of PVA/CS before-after heat treatment and effect after immersion in Glutaraldehyde was investigated by the field emission scanning electron microscopy (SEM). The diameter of PVA/CS 50/50 and 70/30 nanofibers was approximately 190 nm and 580 nm. Fourier Transform Infrared analysis demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…showed that multicarboxylic acids present at high percentages (10% or above) can be used for cross-linking PVA and chitosan; they also found more expression of hydrophobicity in the thus-modified fibers. [ 19 ] Heat treatment was also shown to increase the water insolubility of the PVA/chitosan fibers by Riwu et al, but the combination of the effects of these modifiers, the heat treatments, and the addition of green cross-linking agents (below 5%) have not yet been investigated [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that multicarboxylic acids present at high percentages (10% or above) can be used for cross-linking PVA and chitosan; they also found more expression of hydrophobicity in the thus-modified fibers. [ 19 ] Heat treatment was also shown to increase the water insolubility of the PVA/chitosan fibers by Riwu et al, but the combination of the effects of these modifiers, the heat treatments, and the addition of green cross-linking agents (below 5%) have not yet been investigated [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al, in 2017, showed that two parallel processes can take place: the increase in chitosan content decreased the contact angles, but the cross-linking with glutaraldehyde increased the hydrophobicity of the net [ 26 ]. This process could also be induced by additional heat treatment [ 15 , 32 ] or plasma treatment [ 45 ]. This is also true in the case of the green cross-linker—citric acid [ 46 ]—which was chosen in the present work [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanofibers produced by electrospinning resulted in a smaller diameter than the fibers created by conventional methods [1][2][3] . The electrospinning method produced nanofibers in the range of micrometers until nanometer scale [3][4][5] . These small fibers are potentially using for many applications, such as membrane of filtration and composite materials [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, thermal treatment is used to prepare water-resistant electrospun mats in combination with crosslinking agents such as citric acid and GA intended for wound healing and antibacterial applications. [21,22] As PVA exhibits bioinertness and it tries to modulate the bioactivity by reinforcing of cerium oxide (CO) nanoparticles. The CO belongs to the lanthanide series and the most abundant rare earth metal, also known as nanoceria.…”
Section: Introductionmentioning
confidence: 99%